The Contributing Factors of General Adjustment On Malaysian Expatriates In Construction Industry Overseas - Zainol, Halmi; Mohd Isa, Haryati; Alauddin, Kartina; Mohd Derus, Mohmad (Journal of Surveying, Construction and Property, 2017)
The achievement of Malaysian construction companies create an opportunity to venture abroad. Past reviews have demonstrated that the trouble of expatriates in adjusting to a new environment is the main aspect that leads to the unsuccessful of assignments. The accomplishment in implementing an abroad task does not exclusively rely upon an expatriate’s technical expertise. The adjustment issues, for example, the socializing with the local, communication and culture adaptation also influence on the assignment. The study was conducted to identify the contributing factors of general adjustment on assignment faced by Malaysian executive expatriates in host countries. The purpose of the study was to identify adjustment contributing factors relating to general adjustment abroad. Questionnaires were sent to Malaysian expatriate executives. Sixty four Malaysian expatriate executives from Malaysian construction companies abroad were included in this study. The findings indicate interaction, social adaptation and living condition influence their adjustment abroad. A pre-departure training preparation aspect for expatriate is a good measure before their departure to host nations.